The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.2903/j.efsa.2006.356
|View full text |Cite
|
Sign up to set email alerts
|

Opinion of the Scientific Panel on food additives, flavourings, processing aids and materials in contact with food (AFC) related to a new long‐term carcinogenicity study on aspartame

Abstract: Aspartame has undergone extensive testing in animals and studies in humans, including four animal carcinogenicity studies conducted during the 1970s and early 1980s. These studies, together with studies on genotoxicity, were evaluated by regulatory bodies worldwide and it was concluded that they did not show evidence of genotoxic or carcinogenic potential for aspartame. Since its approval, however, the safety of aspartame has been repeatedly questioned, with discussions focusing not only on the safety of aspar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 35 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…This raises the possibility of an environmental component to the development of lymphoma in these animals. 26 In addition, an interesting consideration would be whether the inflammation associated with chronic respiratory disease could be involved in the development of neoplasia. 27 Two of the rats in the present study were positive for M pulmonis.…”
Section: Discussionmentioning
confidence: 99%
“…This raises the possibility of an environmental component to the development of lymphoma in these animals. 26 In addition, an interesting consideration would be whether the inflammation associated with chronic respiratory disease could be involved in the development of neoplasia. 27 Two of the rats in the present study were positive for M pulmonis.…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion was confirmed by the US FDA, which issued an opinion on April 20, 2007, that APM is not long-term carcinogenic and that it is safe for people to consume APM for a long time. The JECFA under the World Health Organization and the EFSA have evaluated its safety, and the experiments conducted on animals have projected that the daily intake of 2.4 g of APM for a normal healthy population weighing about 60 kg would not cause cancer. However, recent research studies demonstrated new evidence to indicate that APM is a chemical carcinogen in rodents. Whether or not APM is safe needs further experimental determination in detail.…”
Section: Discussionmentioning
confidence: 99%
“…The existing animal experiments have indicated the potential health effect of APM. Recent studies have revealed that APMfed (25,50, and 100 mM) zebrafish hyperlipidemia model exhibited weight gain, hyperglycemia, and acute swimming defects. 20 APM (0.25 g/L) may affect glucose homeostasis and spatial cognition in male mice, 21 while other researchers reported that the no obvious adverse effect concentration (NOAEC) in rats and dogs is up to 4000 mg/kg body weight/ day.…”
Section: Introductionmentioning
confidence: 99%
“…At the heart of this debate were doubts raised about the accuracy of the RI's histopathological diagnoses -in particular the RI's diagnoses of pulmonary lymphomas and leukemiasin animals exposed to aspartame [14,16]. The European Food Safety Agency (EFSA) made the unsubstantiated claim that the RI's animal colony was poorly managed and that the experimental animals were subject to uncontrolled infections [8,9,17]. Schoeb et al speculated further that pulmonary lesions diagnosed as lymphomas and leukemias by RI might have been inflammatory lesions caused by Mycoplasma pulmonis infections [18].…”
Section: The Controversymentioning
confidence: 99%
“…National and international public health agencies need to take careful notice of these revalidated findings. Previous facile dismissals of the carcinogenicity of aspartame can no longer be sustained [8,9,17,18]. Long experience documents that delay in acting on welldocumented evidence of chemical carcinogenesis results in unnecessary disease and preventable death [26][27][28].…”
Section: Implications For Public Health and Cancer Preventionmentioning
confidence: 99%